UPAYA MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN (PKN) MATERI POKOK SISTEM PEMERINTAHAN REPUBLIK INDONESIA MELALUI METODE PEMBELAJARAN MODEL STAD (STUDENT TEAM ACHIEVEMENT DIVISION) PADA SISWA KELAS VI SEMESTER GANJIL SD NEGERI SUKOWINANGUN 4 TAHUN PELAJARAN 2014/2015 - Suryati, Suryati (IKIP PGRI MADIUN, 2015)
Citizenship Lesson is a lesson which focused on how to create a citizen who able to understand and conduct the right and responsibiity in order to be smart, skillfull and characterized citizen which as asked by Pancasila and UUD 1945. But in fact, there are many students who do not interesting with this lesson since most of the teachers give bored method which affected in lesson performance. The research method used is class action research. Population of this study are 10 students of grade 6 SDN Sukowinangun 4 Magetan. Sampling technique in this study is purposive sampling. The independent variables are STAD Methode and the dependent variable is Students Learning Performance.The result of this research is from 10 students there are 9 setudents or 90% who show the increasing in class activity and learning performance. It can be concluded that STAD Methode can increase citizenship lesson on material of government system in Indonesia Republic for sixth grade students of SDN Sukowinangun 4.Â Key Words: STAD methode, students learning performance.